TRANSLOCATION OF TRANSITION METALS DURING THE DEGRADATION OF PINUS RADIATA BY GLOEOPHYLLUM TRABEUM ON THE FOREST SOIL - Pozo, Claudio; Melín, Victoria; Elissetche, Juan Pedro; Contreras, David; Freer, Juanita; Rodríguez, Jaime (Journal of the Chilean Chemical Society, 2016)
Brown rot fungi (BRF) are highly destructive wood degraders characterized by extensive degradation and mineralization of cellulose and hemicellulose, in most of the cases without causing a substantial removal of lignin. BRF have not a complete cellulase complex neither ligninolytic enzymes, therefore, has been hypothesized that to degrade wood components, a non-enzymatic mechanism based on ●OH radicals production through Fenton reaction is also involved. The availability of iron limits the Fenton reaction in wood biodegradation by BRF, because this metal (and other transition metals) is found in small amounts in wood. For this reason, it has been postulated that the fungus transport metals from the soil. To study the effect of soil and transition metal translocation (Fe, Cu, and Mn) on wood biodegradation by the BRF Gloeophyllum trabeum, Pinus radiata wood chips (20 years old) were incubated with forest soil in stationary tray bioreactor for a period until 16 weeks. Translocation of transition metals, mass and wood components (extractives, carbohydrates, and lignin) loss, the decrease of holocellulose viscosity and oxalic acid production were determined at different intervals of time. Wood on soil showed a high translocation of transition metals mainly Fe. Translocation of soil metals into the wood was relevant for improving fungal growth and wood decay, which is correlated significantly with higher loss mass and wood components compared with degradation without soil.